RF Coil Setup for 31P MRSI in Tongue Cancer in vivo at 7 T - Forner, Ria; Nam, Kyungmin; de Koning, Klijs J.; van der Velden, Tijl; van der Kemp, Wybe; Raaijmakers, Alexander; Klomp, Dennis W. J. (Frontiers in Neurology, 2021)
Surgery for tongue cancer often results in a major loss in quality of life. While MRI may be used to minimise the volume of excised tissue, often the full tumour extent is missed. This tumour extent may be detected with metabolic imaging. One of the main reasons for the lack of metabolic information on tongue cancer would be the absence of an x-nuclear coil with the tongue as a focus target. Metabolic MRI through 31P MRSI is known as a powerful tool to non-invasively study elevated cell proliferation and disturbed energy metabolism in tumours. Severe magnetic field non-uniformities are inherently caused by the substantial difference in magnetic susceptibilities of tissue and air in the mouth and its environs. Despite this, the wide chemical shift dispersion of 31P could still facilitate precise detection of the cell proliferation biomarkers, phospomonoesters and diesters, as well as energy metabolites ATP, inorganic phosphate, and phosphocreatine potentially mapped over the tongue or tumour in vivo. In this study, we present the first 31P MRSI data of the human tongue in vivo from healthy volunteers and a patient with a tongue tumour at 7 T MRI using a 1H 8-channel transceiver setup placed inside a body 31P transmitter, which is able to get a uniform excitation from the tongue while providing comfortable access to the patient. In addition, a user-friendly external 31P receiver array is used to provide high sensitivity (80%) comparable to an uncomfortable inner mouth loop coil positioned on the tongue. The primary aim is the demonstration of 31P metabolite profiles in the tongue and the differences between healthy and malignant tissue. Indeed, clear elevated cell proliferation expressed as enhanced phosphomonoesters is observed in the tumour vs. the healthy part of the tongue. This can be performed within a total scan duration of 30 min, comparable to clinical scans, with a spatial resolution of 1.5 cm for the 10-min 31P MRSI scan.